Alternate Sequential Suture Tightening: A Novel Technique for Uncontrolled Postpartum Hemorrhage - Sharda Brata Ghosh; Y. M. Mala (Obstetrics and Gynecology International)
Objective. The most commonly described technique of modified B-Lynch suture may not be suitable for all the patients presenting with flabby, atonic uterus. Study Design. A retrospective analysis of twelve patients with uncontrolled postpartum haemorrhage, who underwent this procedure from March 2007 to September 2012, was conducted. In this novel technique, sutures are passed in the lower uterine segment and are tightened alternately to control uterine bleeding. Results. Average duration of the procedure was 4 minutes (range 2–7 minutes). Average blood loss was 1625 mL (range 1300–1900 mL). Eleven patients (91.66%) were seen to have a successful outcome with only this technique. No patient required hysterectomy and one patient (8.33%) required additional bilateral internal iliac artery ligation. All the patients had a minimum follow-up of 2 yrs and none of them reported any infertility problems. Conclusion. This technique is simple, quick, and effective. There was no adverse effect on the fertility potential for the observed 2 years; however, a long-term follow-up is required to comment on its actual rate. This technique cannot replace the standard modified B-Lynch technique for uncontrolled postpartum haemorrhage but can be used for unresponsive, flabby, and atonic uterus.